Impact of the COVID-19 pandemic on juvenile idiopathic arthritis presentation and research recruitment: results from the CAPRI registry. Issue Volume 61:Issue S12(2020) (29th October 2021) - Dushnicky, Molly J; Campbell, Catherine; Beattie, Karen A; Berard, Roberta; Cellucci, Tania; Chan, Mercedes; Gerschman, Tommy; Johnson, Nicole; Lim, Lillian; Luca, Nadia; Miettunen, Paivi; Morishita, Kimberly A; et al.
Abstract: Objective: The COVID-19 pandemic has disrupted healthcare delivery and clinical research worldwide, with data from areas most affected demonstrating an impact on rheumatology care. This study aimed to characterize the impact of the pandemic on the initial presentation of JIA and JIA-related research in Canada. Methods: Data collected from the Canadian Alliance of Pediatric Rheumatology Investigators JIA Registry from the year pre-pandemic (11 March 2019 to 10 March 2020) was compared with data collected during the first year of the pandemic (11 March 2020 to 10 March 2021). Outcomes included time from symptom onset to first assessment, disease severity at presentation and registry recruitment. Proportions and medians were used to describe categorical and continuous variables, respectively. Results: The median time from symptom onset to first assessment was 138 (IQR 64–365) days pre-pandemic vs 146 (IQR 83–359) days during the pandemic. The JIA category frequencies remained overall stable (44% oligoarticular JIA pre-pandemic, 46.8% pandemic), except for systemic JIA (12 cases pre-pandemic, 1 pandemic). Clinical features, disease activity (cJADAS10), disability (CHAQ) and quality of life (JAQQ) scores were similar between the two cohorts. Pre-pandemic, 225 patients were enrolled, compared with 111 in the pandemic year, with the greatest decrease from March to June 2020. Conclusions: We did not observe the anticipated delay in time to presentation or increased severity at presentation, suggesting that, within Canada, care adapted well to provide support to new patient consults without negative impacts. The COVID-19 pandemic was associated with an initial 50% decrease in registry enrolment but has since improved.